2021
DOI: 10.1108/bpmj-07-2020-0328
|View full text |Cite
|
Sign up to set email alerts
|

Customer process-centric artefacts: a literature review

Abstract: PurposeCompanies that strive to provide customers with value in their processes benefit from artefacts that allow them to better understand customer processes (CPs) and to influence CPs in ways that are valuable for customers. Such CP-centric artefacts (CPCAs) carry various labels across research fields, which inhibit their application or utilization for developing further artefacts. This study provides a structured overview of existing CPCAs and investigates which research foundations promote their developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…The promotion of process improvement, in turn, occurred through the use of continuous improvement projects guided by the operational quality area, which sought to understand, with the leaders of the operational mats, gaps and opportunities identified by the deviations from the service level agreement (SLA), indices of complaints in regulatory bodies and by customer expectations when they are in the service channels. This customer expectation will be referred to in this study as customer voice or customer sentiment (Palvölgyi & Moormann, 2021).…”
Section: Organization Structure and First Process Prioritization Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…The promotion of process improvement, in turn, occurred through the use of continuous improvement projects guided by the operational quality area, which sought to understand, with the leaders of the operational mats, gaps and opportunities identified by the deviations from the service level agreement (SLA), indices of complaints in regulatory bodies and by customer expectations when they are in the service channels. This customer expectation will be referred to in this study as customer voice or customer sentiment (Palvölgyi & Moormann, 2021).…”
Section: Organization Structure and First Process Prioritization Modelmentioning
confidence: 99%
“…The analysis of indicators such as SLA, for example, showed that the process of issuing a real estate credit agreement met the agreed service level, while the client's request was being processed in the back office, but did not include the effective delay; considering that once the product is requested, it is necessary to register it in the real estate registry, among other steps. Given this scenario, the organization promoted a new approach that values customer satisfaction (Kreuzer et al, 2020;Palvölgyi & Moormann, 2021).…”
Section: Change In Organizational Structure and New Process Prioritiz...mentioning
confidence: 99%
See 2 more Smart Citations